(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
objectives of the research. A questionnaire was prepared on the impact of information and communication technology to develop the art of entrepreneurial business skills among scout leaders in Faculties and departments Student activities at Al-Mustansiriya University and learning about the impact of information and communication technology to develop the art of entrepreneurial business skills among the scout leaders in the colleges and department of student activities at Al-Mustansiriya University in light of the Corona pandemic